Tinglado y Mulch en las características agronómicas y el rendimiento en Allium fistulosum L. cebolla china Loreto - Panaifo Pacaya, Geraldo Augusto (2025)
The objective of this study was to evaluate the interaction between shading structures (tinglado) and Mulch on the agronomic characteristics and yield of Allium fistulosum L. (Chinese onion) in the Loreto region, Peru. A randomized complete block design (RCBD) with four replications was used, evaluating combinations of shading at 35% and 50%, no shading, and the presence or absence of Mulch. Variables analyzed included plant height, root length, total plant weight, root and leaf weight, and bulb yield. The results showed that shading had a significant effect on plant height (p < 0.001), with the highest values recorded under no shading conditions (55.80 cm). Root length also showed significant differences (p < 0.01), with longer roots observed in unshaded conditions (9.91 cm). Regarding total plant weight, unshaded conditions with Mulch achieved the highest average of 237.02 g, significantly outperforming shaded treatments (p < 0.001). However, no significant interaction between shading and Mulch was found in any of the variables evaluated. It is concluded that shading predominantly influences vegetative characteristics, while Mulch independently enhances yield. No combined effect of these factors was observed. These results underscore the importance of tailoring these agricultural practices individually to meet specific horticultural management objectives.